AB1601 topline results – Phase 2 study of ABvac40 in patients with amnestic mild cognitive impairment (a‐MCI) or very mild Alzheimer's Disease (Vm‐AD). (20th December 2022) - Molina, Elisabet; Castillo, Sergio; Lacosta, Ana M; Allué, Jose A; Fandos, Noelia; Montañés, María; Romero, Judith; Sarasa, Leticia; Boada, Mercè; Sarasa, Manuel
Abstract: Background: Immunotherapy against amyloid β (Aβ) has emerged as a promising treatment option for Alzheimer's disease (AD). Araclon‐Biotech is developing an active vaccine against Aβ40 peptide, one of the most abundant peptides in senile plaques and the dominant peptide in vascular deposits, that has been associated with earlier onset of dementia. The immunogen peptide of ABvac40 (Aβx‐40) does not contain the epitope recognized by T cells whose activation was considered the primary cause of aseptic meningoencephalitis. In Phase‐1 (NCT03113812), ABvac40 generated a long‐lasting antibody response after only three‐monthly‐immunizations. In 2017 Araclon‐Biotech initiated a Phase‐2, 24‐month, multicenter, randomized, double‐blind, placebo‐controlled trial in patients with a‐MCI or Vm‐AD to investigate the safety, tolerability, and immune response of repeated subcutaneous injections of ABvac40 as well as explore the effect of treatment on biomarkers and cognition (Part A) (NCT03461276). In July 2020, a protocol amendment was approved whereby the blind phase (Part A) was shortened from 24 to 18‐months and an additional 18‐months cross‐over study (Part B) was added. Method: Patients initially receiving placebo during Part A will be crossed over to receive ABvac40, whereas patients initially receiving ABvac40 will be given matching placebo plus a booster. Assignment to treatment groups will remain blinded for investigators and patients until the end of Part B. It is noteworthy that when the blind will be opened (18‐month visit), the average follow‐up will be of 23 months (close to the 24 months initially planned). Result: 124 patients aged 55 to 80 have been included (a‐MCI, n = 80; Vm‐AD, n = 44). Baseline demographics and characteristics were reasonably well balanced. A total of 101 patients have completed Part A and 77 of which have finally transitioned to Part B. Part B is progressing as scheduled. Conclusion: Top line results for Part A will be presented in the congress.